An autosomal glucose-6-phosphate dehydrogenase (hexose-6-phosphate dehydrogenase) polymorphism in human saliva - Tan, Soon Guan; Ashton, G. C. (Karger, 1976)
Glucose-6-phosphate dehydrogenase (hexose-6-phosphate dehydrogenase) from human saliva has been demonstrated by the zymogram technique. Three phenotypes were found. Family and population studies suggested that these phenotypes are the products of an autosomal locus with two alleles Sgd-1 and Sgd-2.